The subject organization and the typology of heroes in the Russian and Belarusian modernist novel in the second half of the XX century - Kriklivets, Elena V. (Journal of the Belarusian State University. Philology, 2018)
Purpose of the article is reveal the ways of subject organization and the typology of heroes in the Russian and Belaru- sian modernist novel in the second half of the XX century. Comparative view of the study revealed general patterns and national specifics of the artistic representation of characters by Russian and Belarusian writers. In the article, the types of heroes represented in the Russian and Belarusian modernist novel in the second half of the XX century are defined and systematized; the main ways of determining the consciousness and behavior of characters are described.
Keywords: Russian literature; Belarusian literature; comparative analysis; modernism; typology of heroes; novel